Comparison Study of Non-Alcoholic Sanitizer and Alcohol Based Sanitizer - Jagdeep Singh; Ankur Thakur; Lovish Sharma; Kavita (Recent Trends in Infectious Diseases, 2024)
Hand sanitizer is the best choice to maintain the hand hygiene and stopping the spread of infectious diseases. The active ingredient in traditional hand sanitizers is usually alcohol, but worries about flammability, skin irritation, and possible abuse have prompted the creation and growing popularity of alcohol-free substitutes. The purpose of this review is to objectively assess the safety, effectiveness, and usefulness of alcohol-free hand sanitizers. To successfully eradicate germs, alcohol-free hand sanitizers rely on substitute active ingredients, such as triclosan, quaternary ammonium compounds, or benzalkonium chloride. Research evaluating the performance of alcohol-free sanitizers against their alcohol-based equivalents has yielded inconsistent findings; some have demonstrated that the two types of sanitizers are equally successful in lowering bacterial counts, while others have highlighted variations in the range and duration of action. Additionally, issues with microbial resistance and the durability of antimicrobial agents on skin have been brought up. Alcohol-free hand sanitizers depend on different active ingredients, like triclosan, quaternary ammonium compounds, or benzalkonium chloride, to effectively kill germs. Research evaluating the performance of alcohol-free sanitizers against their alcohol-based equivalents has yielded inconsistent findings; some have demonstrated that the two types of sanitizers are equally successful in lowering bacterial counts, while others have highlighted variations in the range and duration of action. Additionally, worries have been raised regarding the potential for bacterial resistance and the persistence of antimicrobial agent residue on skin. Safety concerns are quite important, especially when it comes to potential allergies and skin irritation. Formulations without alcohol tend to be less drying and irritating than those with alcohol, which makes them appropriate for daily use for people with sensitive skin. To ascertain the long-term consequences of consistent exposure to various active ingredients, more study is necessary. The practical ramifications encompass evaluations of affordability, usability, and accessibility. In places like hospitals, schools, and other sectors where alcohol-based products are prohibited or unwelcome, alcohol-free hand sanitizers are advantageous. Still, there are obstacles in the way of gaining broad acceptance and guaranteeing adherence to hand hygiene protocols. In comparison to conventional alcohol-based formulations, alcohol-free hand sanitizers show promise as a viable substitute, providing similar effectiveness with maybe less safety risks. To clarify their long-term effects and adjust their formulation for optimal efficacy and consumer acceptance, more research is necessary.
Keywords: Hand hygiene; alcohol; infections; microbial resistance; sanitizer